Reactive arthritis after SARS-CoV-2 infection. Issue 2 (12th September 2022) - Dombret, Sophia; Skapenko, Alla; Schulze-Koops, Hendrik
Abstract : SARS-CoV-2 has been recognised as a potential trigger of inflammatory arthritis in individuals with inflammatory rheumatic diseases as well as in previously unaffected individuals. However, new-onset arthritis after COVID-19 is a heterogeneous phenomenon that complicates differential diagnosis. For example, acute arthritis with features of viral arthritis has been reported after COVID-19, as has crystal-induced arthritis. Arthritides mimicking reactive arthritis (ReA) have also been described, but these patients often do not fulfil the typical features of ReA: several reports describe cases of patients older than 45 years at the onset of arthritis, and the characteristic genetic feature of ReA, HLA-B27, is rarely found. Because viral infections are much less likely to cause ReA than bacterial infections, and respiratory infections are rarely the cause of ReA, it is currently unknown whether SARS-CoV-2 can cause true ReA. Here, we report the case of a 30-year-old patient who presented with acute pain, swelling and redness in the left metatarsophalangeal (MTP) joint and ankle 7 days after resolution of a SARS-CoV-2 infection. Diagnostics revealed arthritis of the MTP2, synovitis of the upper ankle with significant joint effusion and peritendinitis of the flexor tendons. Based on the clinical manifestations and diagnostic test results, ReA appeared to be the most likely cause. A screening for typical ReA-associated infections was negative. The patient was treated with NSAIDs and intra-articular and systemic glucocorticoids. At a follow-up visit after discontinuation of glucocorticoids, the patient was symptom-free. Overall, we observed a ReA with typical clinical, genetic and patient characteristics after SARS-CoV-2 infection, and we conclude that a direct association with COVID-19 is highly plausible.